Expressing Times in Indonesian and English: A Contrastive Study - I Dewa Putu Wijana (BATARA DIDI : English Language Journal, 2022)
This paper deals with the differences and similarities of how Indonesian and English speakers asking about or informing time. By using data collected intuitively and empirically tested with other native speakers, and compared with their English equivalents, it is found that in spite of their few similarities, both languages that belong to different language family group, show a lot structural and pragmatic differences with regard to asking about and informing times, of either precise and non-prise ones.